2015
DOI: 10.18805/asd.v35i4.6862
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis studies for yield and fiber quality traits in intra hirsutum hybrids of cotton (<italic>Gossypium hirsutum</italic> L.)

Abstract: The present study was performed to evaluate the heterosis effects for seed cotton yield and fiber quality traits of 56 hybrids and their parents involving seven lines and eight testers along with a check at Acharya N.G. Ranga Agricultural University, Hyderabad. The results showed that, range of relative heterosis varied from -3.40 to 13.29 in ginning percentage, -5.28 to 14.10 in 2.5% span length, -8.72 to 8.25 in uniformity ratio, -16.39 to 14.88 in micronaire value, -5.97 to 10.02 in bundle strength and -32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…The best heterotic combinations identified were HYPS-152 × GSHV-177, L1493 × SCS-1207 and L1493 × GTHV-13/32 over mid parent, better parent and standard check for bundle strength. These results are in conformity with the reports of Sekhar et al (2012), Kumar et al (2013) and Srinivas and Bhadru (2015).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The best heterotic combinations identified were HYPS-152 × GSHV-177, L1493 × SCS-1207 and L1493 × GTHV-13/32 over mid parent, better parent and standard check for bundle strength. These results are in conformity with the reports of Sekhar et al (2012), Kumar et al (2013) and Srinivas and Bhadru (2015).…”
Section: Resultssupporting
confidence: 94%
“…The hybrid combinations, viz., HYPS-152 × SCS-1207,(L770 × GSHV-177, SCS-1207 × PBH-13, SCS-1207 × GJHV-497, SCS-1207 × GSHV-177, SCS-1207 × GTHV 13/32, PBH-13 × GJHV-497, PBH-13 × L1231, GSHV-177 × GTHV-13/32 and GSHV-177 × L1231 exhibited a significant positive heterosis over mid parent, better parent and standard check. These results are in agreement with the findings of Balu et al (2012), Sekhar et al (2012), Maria et al(2012, Patel et al(2012), Kumar et al(2013), Nassar (2013, Srinivas and Bhadru (2015), Abdul et al(2016) and Jayshankar (2017) who had reported a significant positive heterosis for seed cotton yield plant -1 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The crosses viz., SCS-1207 × L1231, L1493 × GTHV-13/32 and GSHV-177 × L1231 were identified as the best heterotic combinations over mid parent, better parent and standard check for ginning outturn. These results are in accordance with the findings of Sekhar et al (2012) [12] , Kumar et al (2013) [6] , Srinivas and Bhadru (2015) [13] and Abdul et al (2016) [2] . In the present study based on per se performance and significant standard heterosis the crosses, SCS-1207 × GSHV-177, GSHV-177 × L1231 and SCS-1207 × PBH-13 were found to be promising for seed cotton yield plant -1 .…”
Section: Methodssupporting
confidence: 93%
“…Average heterosis was found positive for all the traits in both straight and reciprocal cross combinations except for number of sympods for which mean for reciprocal effects was found to be negative. Several workers have reported similar type of results for economic traits in cotton (Choudhary et al 2014, Srinivas and Bhadru 2015.…”
Section: Average and Standard Heterosismentioning
confidence: 56%